Identification of Waist Circumference, Hip Width, Chest Width, and Chest Depth Measurements of Female Priangan Sheep at SP3TDK Tambak Mekar Subang Regency - Gunawan, Deden Rizwan; Heriyadi, Denie; Indrijani, Heni (Jurnal Produksi Ternak Terapan, 2025)
Priangan sheep are a local Indonesian sheep breed that has good environmental adaptability and high economic value, measuring these morphometric characteristics is important as a selection effort for breeding Priangan sheep, especially at SP3TDK Tambak Mekar, which is a breeding unit and development center for Priangan sheep in West Java. Body measurements that can be measured include waist circumference, waist width, chest width, and chest depth. The purpose of this study was to identify the body size of female Priangan sheep at SP3TDK. The research method was a census with 50 female Priangan sheep, 6 months and <1 year, and >1-2 years old, measurements using measuring tapes and caliper sticks. Data were processed using descriptive statistics, which include minimum, maximum, average, standard deviation, and coefficient of variation. The average value of sheep body size is known to increase with age, the body size of Priangan female sheep in SP3TDK at the age of 6 months and <1 year, and >1-2 years respectively, namely waist circumference 59.75 ± 5.35 cm and 68.48 ± 4.54 cm, hip width 13.07 ± 1.29 cm and 14.97 ± 1.29 cm, chest width 14.10 ± 1.11 cm and 15.88 ± 1.22 cm, and chest depth 24.00 ± 1.99 cm and 27.51 ± 1.51 cm.